Changes in Body Size during Early Growth Are Independently Associated with Arterial Properties in Early Childhood - Juan M. Castro; Mariana Marin; Agustina Zinoveev; Victoria García-Espinosa; Pedro Chiesa; Daniel Bia; Yanina Zócalo (Journal of Cardiovascular Development and Disease, 2021)
Nutritional status in early life stages has been associated with arterial parameters in childhood. However, it is still controversial whether changes in standardized body weight (z-BW), height (z-BH), BW for height (z-BWH) and/or body mass index (z-BMI) in the first three years of life are independently associated with variations in arterial structure, stiffness and hemodynamics in early childhood. In addition, it is unknown if the strength of the associations vary depending on the growth period, nutritional characteristics and/or arterial parameters analyzed. Aims: First, to compare the strength of association between body size changes (Δz-BW, Δz-BH, Δz-BWH, Δz-BMI) in different time intervals (growth periods: 0–6, 0–12, 0–24, 0–36, 12–24, 12–36, 24–36 months (m)) and variations in arterial structure, stiffness and hemodynamics at age 6 years. Second, to determine whether the associations depend on exposure to cardiovascular risk factors, body size at birth and/or on body size at the time of the evaluation (cofactors). Anthropometric (at birth, 6, 12, 24, 36 m and at age 6 years), hemodynamic (peripheral and central (aortic)) and arterial (elastic (carotid) and muscular (femoral) arteries; both hemi-bodies) parameters were assessed in a child cohort (6 years; n =632). The association between arterial parameters and body size changes (Δz-BW, Δz-BH, Δz-BWH, Δz-BMI) in the different growth periods was compared, before and after adjustment by cofactors. Results: Δz-BW 0–24 m and Δz-BWH 0–24 m allowed us to explain inter-individual variations in structural arterial properties at age 6 years, with independence of cofactors. When the third year of life was included in the analysis (0–36, 12–36, 24–36 m), Δz-BW explained hemodynamic (peripheral and central) variations at age 6 years. Δz-BH and Δz-BMI showed limited associations with arterial properties. Conclusion: Δz-BW and Δz-BWH are the anthropometric variables with the greatest association with arterial structure and hemodynamics in early childhood, with independence of cofactors.